Strategies for Effective Health Services Management in Hospitals: A Systematic Review of Key Models and Practices - Lsloum, Muqrin Mana Ali; Alyami, Jaber misfer Hadi; Alsleem , Mohammed Ali Mana; Alsleam, Mahdi Hamad Mahdi; Al-saloom, Saleh Mohammed Agal; Alwadai, Mohammed Saeed Saleh; Alyami, Jaber Hussain Munaser; Rabou, Abdulaziz Saeed Saleh; aldhalei, Majed Abdullal; alajmi, hussain saad rashed (Journal of Ecohumanism, 2024)
Background: Effective health services management is critical in hospitals, where the demands for improved patient outcomes, operational efficiency, and cost containment are paramount. Over the years, several management models and practices have been implemented in hospital settings, with varying degrees of success. Objective: This systematic review aims to examine and synthesize key models and practices in health services management that have proven effective in enhancing hospital performance, focusing on their impact on patient care, staff efficiency, and operational outcomes. Methods: A systematic literature search was conducted across major databases, including PubMed, Scopus, and Google Scholar, using keywords such as "hospital management," "health services management," and "patient care models." Studies were included if they focused on hospitals, were published in the past ten years, and evaluated the effectiveness of management practices. Results: The review identified several effective management models, including Lean Management, Six Sigma, Patient-Centered Care, Workflow Optimization, and Total Quality Management (TQM). Key practices contributing to successful management included leadership engagement, technology integration, performance measurement, and patient safety protocols. These strategies collectively improved patient satisfaction, reduced wait times, and enhanced hospital efficiency. Conclusion: This review highlights evidence-based management strategies that have a significant impact on hospital operations and patient care. Implementing these practices can help hospital administrators optimize resources, improve staff productivity, and enhance patient experiences.